2023
DOI: 10.3390/polym15234534
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Ductility of Environmentally Friendly Poly(lactide) Composites with Posidonia oceanica Wastes Plasticized with an Ester of Cinnamic Acid

Alejandro Barandiaran,
Diego Lascano,
Nestor Montanes
et al.

Abstract: New composite materials were developed with poly(lactide) (PLA) and Posidonia oceanica fibers through reactive extrusion in the presence of dicumyl peroxide (DCP) and subsequent injection molding. The effect of different amounts of methyl trans–cinnamate (MTC) on the mechanical, thermal, thermomechanical, and wettability properties was studied. The results showed that the presence of Posidonia oceanica fibers generated disruptions in the PLA matrix, causing a decrease in the tensile mechanical properties and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…The possibility of using green composites based on polymeric matrices by incorporating polymers with animal or vegetal marine wastes could be a solution for the biodegradability of materials [8]. Alejandro Barandiaran et al [9] fabricated composites with poly(lactide) (PLA) and Posidonia oceanica fibers using reactive extrusion in the presence of dicumyl peroxide (DCP) and subsequent injection molding. Field emission scanning electron microscopy (FESEM) showed that the reactive extrusion enhanced PO/PLA interaction which diminished the gap between the fibers and the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of using green composites based on polymeric matrices by incorporating polymers with animal or vegetal marine wastes could be a solution for the biodegradability of materials [8]. Alejandro Barandiaran et al [9] fabricated composites with poly(lactide) (PLA) and Posidonia oceanica fibers using reactive extrusion in the presence of dicumyl peroxide (DCP) and subsequent injection molding. Field emission scanning electron microscopy (FESEM) showed that the reactive extrusion enhanced PO/PLA interaction which diminished the gap between the fibers and the matrix.…”
Section: Introductionmentioning
confidence: 99%